Pemberdayaan Pekerja Perempuan dan Anak pada Pasar Tenaga Kerja Digital Era Gig Economy: Kerangka Hukum untuk Masa Depan yang Lebih Aman - Nurhayati, Tri; Hukmu Adila, Arina; Fibriani, Riza Fibriani (Jurnal Risalah Hukum, 2024)
The digital labor market has introduced profound changes to employment practices, presenting both new opportunities and heightened risks for women and children. This article examines the essential role of legal frameworks in empowering these vulnerable groups and ensuring their protection within this evolving landscape. It begins by exploring existing legal standards and international conventions, such as the International Labour Organization (ILO) conventions and United Nations guidelines, which provide foundational principles for labor rights and protections. The article then evaluates the effectiveness of current regulations in addressing specific challenges faced by women and children in digital work environments, including issues of exploitation, harassment, and discrimination. By analyzing case studies and policy implementations, the research highlights the gaps in existing legal frameworks and proposes comprehensive legal reforms aimed at enhancing safety and inclusivity. The article advocates for the adoption of adaptive and forward-looking legal measures that reflect the realities of the digital era, ensuring that women and children are protected and empowered in the future workforce. In conclusion, reinforcing legal frameworks is crucial for fostering a safer and more equitable digital labor market for all.